Cognitive strategy training for adults with neurological conditions: a systematic review and meta-analysis exploring effect on occupational performance. (December 2020) - Swanton, Ruth; Gustafsson, Louise; Froude, Elspeth; Hodson, Tenelle; McInerney, Michelle; Cahill, Liana S; Lannin, Natasha A
Introduction: The objective of this systematic review was to synthesise the evidence for cognitive strategy training to determine its effectiveness to improve performance of activities of daily living in an adult neurological population. Method: Medline, CINAHL, EMBASE, PSYCInfo, PsycBITE and Cochrane Central Register of Controlled Trials and Cochrane Database of Systematic Reviews were searched until August 2019. Studies examining the effect of cognitive strategy training on functional performance were included. Population criteria included adults with non-progressive neurological conditions. External and internal validity of included studies was systematically evaluated using an appropriate methodological quality assessment for each study design. A content analysis was conducted of the methodologies used. Findings: Forty-one studies met the inclusion criteria and were appraised for content, 16 randomised or quasi-randomised trials were meta-analysed. Trial quality was generally 'good', Physiotherapy Evidence Database scale scores ranged from 3 to 8 (out of 10). For activity performance outcomes post-intervention, there was a significant benefit of cognitive strategy training over usual care (standardised mean difference 0.79, 95% confidence interval 0.49–1.09; P < 0.00001). Conclusion: More high-quality research is needed to strengthen the evidence base for cognitive strategy interventions to improve activity performance outcomes for adults with non-progressive neurological conditions. Systematic review registration: PROSPERO CRD42016033728